2019
DOI: 10.3390/cancers11091277
|View full text |Cite
|
Sign up to set email alerts
|

Long Pentraxin-3 Follows and Modulates Bladder Cancer Progression

Abstract: Bladder tumors are a diffuse type of cancer. Long pentraxin-3 (PTX3) is a component of the innate immunity with pleiotropic functions in the regulation of immune response, tissue remodeling, and cancer progression. PTX3 may act as an oncosuppressor in different contexts, functioning as an antagonist of the fibroblast growth factor/fibroblast growth factor receptor (FGF/FGFR) system, rewiring the immune microenvironment, or acting through mechanisms not yet fully clarified. In this study we used biopsies and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Indeed, when compared to tyrosine kinase FGFR inhibitors, NSC12 is characterized by a reduced toxicity that may result in a more favorable therapeutic window [ 54 ]. Here we show that NSC12 inhibits the proliferation of FGF-dependent murine prostate cancer TRAMP-C2 cells, human bladder carcinoma 5637 cells, and murine fibrosarcoma MC17-51 cells (see also [ 26 , 27 , 37 ]) and that this inhibition is paralleled by the elongation of the primary cilium in all the cell lines tested. These data were confirmed in vivo, where NSC12 was able to inhibit tumor growth, and to induce a ciliogenic effect in TRAMP-C2 tumor grafts.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Indeed, when compared to tyrosine kinase FGFR inhibitors, NSC12 is characterized by a reduced toxicity that may result in a more favorable therapeutic window [ 54 ]. Here we show that NSC12 inhibits the proliferation of FGF-dependent murine prostate cancer TRAMP-C2 cells, human bladder carcinoma 5637 cells, and murine fibrosarcoma MC17-51 cells (see also [ 26 , 27 , 37 ]) and that this inhibition is paralleled by the elongation of the primary cilium in all the cell lines tested. These data were confirmed in vivo, where NSC12 was able to inhibit tumor growth, and to induce a ciliogenic effect in TRAMP-C2 tumor grafts.…”
Section: Discussionmentioning
confidence: 84%
“…Alterations of primary cilia may contribute to cancer progression [ 11 , 12 ]. Based on the results obtained in ptx3b zebrafish morphants and the well-known impact of PTX3 on FGF-dependent tumors [ 23 , 24 , 25 , 26 , 27 , 37 ], we decided to investigate whether the modulation of PTX3 expression may affect primary cilia in FGF-dependent cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These comprehensive innovative analyses have led to new molecular classification based on the genomic expression profiles and the discovery of potential diagnostic and therapeutic molecular targets. The current special series includes 11 articles by international leading researchers who are involved in the investigation of several challenging issues, particularly novel potential biomarkers in GU cancers, using a variety of innovative approaches [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
mentioning
confidence: 99%
“…Long pentraxin-3 (PTX3) is a member of the pentraxin family which regulates tumor progression through cell proliferation, angiogenesis, mobility, and immune modulation. Matarazzo et al evaluated the differential expression of PTX3 during BC progression in cell lines, animal models, and patient samples and found that PTX3 modulation and the consequent impairment of FGF/FGR systems in BC cells have a significant impact on BC growth [ 8 ]. In addition, Ide et al reviewed the role of steroid hormone receptors, such as androgen receptor, estrogen receptor-α, estrogen receptor-β, glucocorticoid receptor, progesterone receptor, and vitamin D receptor, in urothelial tumorigenesis [ 11 ].…”
mentioning
confidence: 99%